An Assessment of the Implementation of Performance Budgeting in Poland with Reference to the Experiences of Other Countries - Guziejewska, Beata (Comparative Economic Research. Central and Eastern Europe, 2013)
Since the last global financial crisis, public expenditures have been experiencing increasing budget constraints. Therefore, public authorities search for solutions that would foster efficient and transparent expenditures at both the national and local government levels. One of the tools at their disposal is the performance-based budget, which is not, however, cheap or easy to implement. The aim of this paper is an assessment of the implementation of performance budgeting in Poland, and a formulation of proposals de lege ferenda. The assessment discusses selected aspects and conclusions which emerge from the experiences of other countries. The main thesis, set forth in the conclusion of this article, is that in many countries, including Poland, the implementation of a performance-based budget takes place at the national level, not at the local government level, which seems to be questionable, or even incorrect.